(untitled) (The International Research Journal of Management Science, 2021)
Commercial banks have a pivotal role in an economy as they provide easy access for firms to fulfill financing needs and help stimulate economic development. This study aims to analyze the impact of key bank-specific determinants on bank value in Nepalese commercial banks, covering 133 observations from 19 commercial banks over the period 2012/13 to 2018/19. Bank value is measured through M/B and Tobin’s Q. Size, profitability, credit risk, loan, deposit and capital are used as explanatory variables. Panel data regression models have been used for analysis purpose. The results of this paper show that profitability, deposit and loans are major determinants of bank value. Moreover, return on assets and bank deposit have positive effect on bank value whereas loan has negative explaining power on bank value. Thus, this paper concludes that Nepalese commercial banks have to pay special attention for the efficient and effective utilization of assets to increase profits and try to increase the size of deposits to increase loan portfolio. Steps and enforcement actions need to be taken by policy level authorities for effective loan management to minimize credit risk and increase bank value.